Menstrual pattern and anthropometric characteristics of women with primary and secondary infertility in comparison with age-matched controls - Manavi Singh; Vijayan Sharmila; Priyanka Yoga; Vinod K Kalidoss (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: The incidence of infertility has increased significantly due to lifestyle changes and the presence of diverse environmental stress. Body mass index (BMI) and waist circumference (WC) are two common anthropometric measures of obesity. Factors such as differences in race, sex, and age influence BMI, and recent studies have reported limitations in the use of BMI to determine obesity. Body fat distribution has a more valid criterion for determining obesity than BMI. Our aim was to compare the menstrual pattern and anthropometric parameters of women with primary and secondary infertility with those of age-matched controls and to assess the correlation between the anthropometric variables and fertility types. MATERIALS AND METHODS: A cross-sectional study was conducted in which the anthropometric measurements and menstrual history over the last 3 months of cases of primary and secondary infertility were compared with the age-matched control group. RESULTS: Women with primary and secondary infertility tend to be overweight or obese. The menstrual pattern of women with infertility was not statistically different as compared to the control groups. There were significant differences in weight, BMI, hip circumference, WC, and neck circumference (NC) of women with primary infertility with those of age-matched controls. A statistically significant difference was noted in NC between the primary and secondary infertility groups. CONCLUSION: The results obtained show that women with infertility tend to be overweight/obese. Due to the limited sample size, the relationship between menstrual pattern and anthropometric characteristics such as waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), and frame size (FRS) and infertility could not be established.